Chrystianizacja Anglii według "Historia ecclesiastica gentis Angelorum" Bedy Czcigodnego - Kołodziejczyk, Dorota (Annales Missiologici Posnanienses, 2020)
Bede Venerable from Northumbria belongs to the group of the most prolific writers of the early medieval period. This Benedictine friar from Britain became famous thanks to his chronicle: Historia ecclesiastica gentis Angelorum, dedicated to the history of his motherland since the moment of Gaius Julius Caesar’s arrival until the year 731. Thanks to this chronicle, but also his other historical records concerning, e.g. Benedictine abbots, Bede Venerable owes his name of ‘the father of English historiography’. The issue of the Christianisation of Britain, connected with the continuous sending of missionaries on the British territory, creates the main part of this chronicle. This article is an attempt, undertaken with a certain amount of timidity, to outline the history of the introduction and renewal of Christianity in Britain based only on the chronicle written by Bede Venerable.